2014
DOI: 10.1007/s40435-014-0120-7
|View full text |Cite
|
Sign up to set email alerts
|

Observability for optimal sensor locations in data assimilation

Abstract: In this paper we will discuss the application of observability to the planning of sensor configurations in numerical weather prediction (NWP). The dimensions used in NWP make conventional definitions of observability impractical. For this reason we will rely partial observability which is obtained using dynamic optimization to approximate the observability. Using this metric we will form an optimization problem to select sensor configurations that maximize the partial observability of the dynamical system. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Our results suggest that while a high observation density is essential for improving the performance of a model with data assimilation, it is crucial to consider other factors such as the quality of the data and the location of the sensors. Different techniques of observation localization allow optimizing the number of sensors to improve the data assimilation or other data fusion techniques [41][42][43][44]. We highly recommend implementing these techniques in the development of new low-cost monitoring networks.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that while a high observation density is essential for improving the performance of a model with data assimilation, it is crucial to consider other factors such as the quality of the data and the location of the sensors. Different techniques of observation localization allow optimizing the number of sensors to improve the data assimilation or other data fusion techniques [41][42][43][44]. We highly recommend implementing these techniques in the development of new low-cost monitoring networks.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that while a high observation density is essential for improving the performance of a model with data assimilation, it is crucial to consider other factors such as quality of the data and the location of the sensors. Different techniques of observation localization allow optimizing the number of sensors to improve the data assimilation or other data fusion techniques (Alexanderian, Petra, Stadler and Ghattas, 2016;King, Kang and Xu, 2015;Mazzoleni, Alfonso and Solomatine, 2017;Yildirim, Chryssostomidis and Karniadakis, 2009). We highly recommend implementing these techniques in the development of a new low-cost network.…”
Section: Discussion and Commentsmentioning
confidence: 99%
“…. The empirical observability Gramian is used in model reduction [2], [3] for nonlinear systems, and sensor placement problem [13]- [15].…”
Section: B Empirical Observability Gramianmentioning
confidence: 99%